ABDULLA ORIPOV IMAGE THE SKILL OF CREATION - Sh. Isayeva (Galaxy International Interdisciplinary Research Journal, 2022)
Abdulla Aripov’s drama “Sahibkiron” reflects the interpretation of personality, the intersection of spirits between individuals, and the celebration of justice, the ideas that flow into enlightenment. Abdulla Aripov’s mastery of image creation, conflicts between images, the author’s depiction of the spirit of that period in the play. There is a unique interpretation of the drama and the image of Sahibkiran as a person.